Proliferation of Protocorm-Like Bodies of Dendrobium mannii and Dendrobium mirbelianum in Chitosan-containing Media In Vitro - Rahmah, Syifaur; Wiendi, Ni Made Armini; Suwarno, Willy B.; Krisantini, Krisantini (Department of Agronomy and Horticulture, IPB University, 2015)
Dendrobium mannii and Dendrobium mirbelianum were rare and endangered orchid species. In vitro micro propagation could be used to conserve and proliferate these species. The aims of this study were to determine the effects of chitosan on proliferation of the protocorm-like-bodies (PLBs) of in vitro grown Dendrobium mannii and D. mirbelianum. Chitosan has been reported as an important component to promote orchid growth in vitro. In this study chitosan was included in the in-vitro media at the concentrations of 0, 1, 2, 3, and 4 mg.L-1. The highest PLBs formation, clump diameter, and fresh weight on D. mannii were obtained from explants cultured on medium supplemented with 1 mg.L-1 chitosan. After 14 weeks of culture, fresh weight, clump diameter and average number of PLBs of D.mannii were 29.52 %, 33.00 % and 35.88% greater at chitosan (1 mg.L-1) compared to control media. D. mirbelianum treated with low chitosan concentrations (1 and 2 mg.L-1) had 65.71% more leaves than those without chitosan treatment. Chitosan, however, had an adverse effects on growth of both species at 4 mg.L-1. Medium contain 4 mg.L-1 chitosan induced PLBs proliferation of D.mannii, but inhibited PLBs proliferation of D.mirbelianum. These results suggested that chitosan had important roles in PLB proliferation and could be used for the propagation of D. mannii PLBs in vitro. Keywords: rare orchid species, in-vitro